Characteristics of Clinically Asymptomatic Patients with SARS-CoV-2 Infections, Case Series. Issue 1 (17th February 2021) - Goldenfeld, Miki; Nir-Paz, Ran; Segal, Gadi; Bar-On, Elhanan; Mendelson, Ella; Mandelboim, Michal; Wolf, Dana G.; Marom, Edith M.; Israely, Tomer; Achdout, Hagit; Rahav, Galia; Hanage, W.P.; et al.
Abstract: Up until now, there is much debate about the role of asymptomatic patients and pauci-symptomatic patients in severe acute respiratory syndrome novel coronavirus 2 (SARS-CoV-2) transmission, and little is known about the kinetics of viral ribonucleic acid (RNA) shedding in these populations. This article aims to describe key features and the nature of asymptomatic and pauci-symptomatic SARS-CoV-2 infected patients. The cohort consisted of six participants, three pairs, which were infected with SARS-CoV-2 during February 2020 on board the Diamond Princess. Of the six confirmed (reverse transcription polymerase chain reaction [RT-PCR]) cases, four were initially diagnosed in Japan and two upon their arrival to Israel. Duration of infection was between four days and up to 26 days. Of the six patients, three were completely asymptomatic and the others were pauci-symptomatic. All five patients in whom a computerized tomography (CT) scan was performed had lung pathology. In one patient, infectivity was tested using cell culture and a cytopathic effect was demonstrated. A serology test was performed in three of the patients and all three had a positive immunoglobulin G (IgG) four to eight weeks after disease onset. This case series demonstrates that asymptomatic and pauci-symptomatic patients may play a role in infection transmission by demonstrating probable transmission among asymptomatic spouses and by demonstrating a viable virus via a cell culture. Additionally, asymptomatic and pauci-symptomatic patients can have lung pathology and developing IgG antibodies.